2016
DOI: 10.1177/1078155216655474
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ramucirumab in the treatment of cancer – A review of literature

Abstract: Ramucirumab is a recombinant human monoclonal antibody and is used in the treatment of advanced malignancies. Its mechanism of action is by inhibiting angiogenesis in tumor cells by targeting the vascular endothelial growth factor receptor 2. United States Food and Drug Administration (FDA) approved it initially in 2014 for the treatment of advanced gastric or gastro-esophageal junction adenocarcinoma and metastatic non-small cell lung carcinoma. It was approved by FDA in 2015 for the treatment of advanced col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…Ramucirumab, a monoclonal antibody, targets the extracellular domain of VEGFR-2, while other therapeutic agents such as bevacizumab (Avastin) and Sorafenib target the VEGF-A ligand or the intracellular kinase domain of the receptor, respectively. 27 Despite evidence of promising clinical responses to anti-angiogenesis drugs, their successes are restricted by insufficient efficacy and development of refractory tumors and resistance. 28 Understanding the N -glycosylation of VEGFR-2 may offer insight into the role of N -linked glycans in VEGFR-2 function and possible links between insufficient efficacy and refractoriness of anti-angiogenesis therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Ramucirumab, a monoclonal antibody, targets the extracellular domain of VEGFR-2, while other therapeutic agents such as bevacizumab (Avastin) and Sorafenib target the VEGF-A ligand or the intracellular kinase domain of the receptor, respectively. 27 Despite evidence of promising clinical responses to anti-angiogenesis drugs, their successes are restricted by insufficient efficacy and development of refractory tumors and resistance. 28 Understanding the N -glycosylation of VEGFR-2 may offer insight into the role of N -linked glycans in VEGFR-2 function and possible links between insufficient efficacy and refractoriness of anti-angiogenesis therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The relationship, however, between VEGFR2 and ECMs in the tumor tissue is not well validated. On the other hand, abundant ECMs are a typical symptom for fibrotic diseases in noncancerous tissues, such as cirrhosis of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The prospects of targeted therapy as a promising new tool in the therapeutic arsenal of GC were further supported by the approval of ramucirumab by the FDA in 2014 as a second‐line treatment alone or in combination with paclitaxel for patients with local relapse or metastatic gastric cancer . Ramucirumab is a fully humanized monoclonal antibody that antagonizes vascular endothelial growth factor (VEGFR)‐2 and inhibits angiogenesis in tumour cells . The inclusion of ramucirumab was based on the positive results of the phase III REGARD and phase III RAINBOW trials, which demonstrated improved median PFS and overall survival (OS) benefits.…”
Section: Advances In Targeted Therapy In Gastric Cancer: the Trastuzamentioning
confidence: 99%
“…36 Ramucirumab is a fully humanized monoclonal antibody that antagonizes vascular endothelial growth factor (VEGFR)-2 and inhibits angiogenesis in tumour cells. 37 The inclusion of ramucirumab was based on the positive results of the phase III REGARD 38 and phase III RAINBOW trials, 39 which demonstrated improved median PFS and overall survival (OS) benefits.…”
Section: Advances In Targeted Therapy In Gastric Cancer: the Trastumentioning
confidence: 99%